PENGARUH WORD OF MOUTH POSITIF TERHADAP KEPUTUSAN KONSUMEN DALAM MENGGUNAKAN JASA ELLA SKIN CARE DENGAN PERCEIVED QUALITY SEBAGAI VARIABEL MEDIASI - SL. Triyaningsih, Fitri Tensiya Kusumaningrum (JURNAL EKONOMI DAN KEWIRAUSAHAAN, 2015)
Purpose of this research to analyze effect of positive word of mouth on consumer decision with perceived quality as mediation variable. Design research are survey. Population are consumer of Ella Skin Care. Samle used 50 consumer with convenience sampling. This type of data is qualitative data and quantitative data. Source of data used primary data and secondary Collected data technique use questionnaires, observation and documentation. Analysis technique used path analysis. The result showed positive word of mouth has significant effect on consumer decision. Positive word of mouth has significant effect on perceived quality. Positive word of mouth has significant effect on consumer decision with perceived quality as mediation variable. Keywords: positive word of mouth, consumer decision, perceived quality